Improving Reproductive Health in Adolescent Girls at SMK Bhakti Asih Through Herbal Plant Consumption - Rosanti, Aan (CV. Publikasi Indonesia, 2025)
Background: Adolescent girls are prone to reproductive health disorders such as menstrual pain (dysmenorrhea), irregular cycles, and lack of knowledge about reproductive health. One of the non-pharmacological efforts that can be made is the consumption of herbal plants that contain natural compounds to help hormonal balance. Objective: To determine the effect of herbal plant consumption on improving reproductive health in adolescent girls at SMK Bhakti Asih. Methods: Quantitative research with a pre-experimental design of one group pretest-posttest. A sample of 30 female students was selected using purposive sampling. The intervention was in the form of consumption of sour turmeric herbal drinks and red ginger for 4 weeks. Data were analyzed using paired t-test. Results: The average reproductive health knowledge increased significantly (p < 0.05), the regularity of the menstrual cycle improved, and the intensity of menstrual pain decreased from a score of 6.2 to 3.8 on the VAS scale. Conclusion: Consumption of herbal plants has been shown to improve the reproductive health of adolescent girls.